2018
DOI: 10.31393/morphology-journal-2018-24(3)-01
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of sonographic parameters of the kidneys in practically healthy women of the middle intermediate somatotype depending on the constitutional parameters of the body

Abstract: The scientific literature presents quite a large number of works, in which the priority role of mathematical modeling in providing high-quality medical care, health and active longevity of a person is determined. The purpose of the work is to construct and analyze the regression models of individual sonographic sizes of kidneys in practically healthy women of the middle intermediate somatotype, depending on the features of the anthropometric and somatotypological indicators. Within the framework of the agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The regression models of sonographic sizes of the kidneys, depending on the peculiarities of anthroposomatotypological parameters of the body of practically healthy men of mesomorphic, ecto-mesomorphic and endomesomorphic somatotypes, as well as practically healthy women of mesomorphic, ectomorphic, endo-mesomorphic and mean intermediate somatotypes were constructed and presented by us in the previous publications [5][6][7][36][37][38]. To analyze the asymmetry of entering the regression models of sonographic sizes of the anthropo-somatotypological indicators, we took into account all constructed reliable models, and not only models with a determination coefficient of greater than 0.6.…”
Section: Resultsmentioning
confidence: 99%
“…The regression models of sonographic sizes of the kidneys, depending on the peculiarities of anthroposomatotypological parameters of the body of practically healthy men of mesomorphic, ecto-mesomorphic and endomesomorphic somatotypes, as well as practically healthy women of mesomorphic, ectomorphic, endo-mesomorphic and mean intermediate somatotypes were constructed and presented by us in the previous publications [5][6][7][36][37][38]. To analyze the asymmetry of entering the regression models of sonographic sizes of the anthropo-somatotypological indicators, we took into account all constructed reliable models, and not only models with a determination coefficient of greater than 0.6.…”
Section: Resultsmentioning
confidence: 99%
“…The use of regression analysis makes it possible to create mathematical equations for determining the appropriate parameters of various organs and systems [3,11,18], in particular for spirometric forecasting, where predictors are anthropometric and somatotypological variables [4,7]. Despite the fact that there are separate works in which mathematical modeling of external breathing indicators is performed [1,8,15], this does not negate the expediency of such studies, especially for certain ethno-territorial population groups of a certain age, sex, health status, constitutional type, because it will make it possible to establish reference values of spirometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the conditionality of the macro-and microstructure of individual organs of various systems of the human body does not cause objections [8,19]. In addition, modern studies have proven the existence of a mutually determined relationship between the features of the external structure of the body and functional parameters [3]. But it should be noted that the majority of such studies focus on the cardiovascular system [10,11,13,18,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] In general, these studies aimed to develop prediction formulas by calculating the correlation or regression between body composition or various anthropometric parameters and organ sizes. [ 8 ] One study found a significant correlation between kidney size and body mass index and body weight. [ 9 ] Another study found an assignable variation between 11.8 and 22.4% between kidney sizes of healthy adult women and men with an endomesomorphic body type determined using somatotype components and multiple anthropometric parameters such as skinfold thickness and circumference measurements.…”
mentioning
confidence: 99%